2022
DOI: 10.1136/thoraxjnl-2021-217709
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, treatment and survival of malignant pleural and peritoneal mesothelioma: a population-based study

Abstract: IntroductionMalignant mesothelioma (MM) is an aggressive cancer that primarily arises from the pleura (MPM) or peritoneum (MPeM), mostly due to asbestos exposure. This study reviewed the Dutch population-based incidence, treatment and survival since the national ban on asbestos in 1993.Materials and methodsPatients with MPM or MPeM diagnosed from 1993 to 2018 were selected from the Dutch cancer registry. Annual percentage change (APC) was calculated for (age-specific and sex-specific) revised European standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…this is similar to the correlation found in chinese study involving 1110 MPM patients showing median survival time was 17, 13, 12, 8, 6, 5 months for IA, IB, II, IIIA, IIIB, and IV, respectively (19) . This is also evident in a Dutch study conducted among 12,168 patients showed that patients diagnosed with stage I pleural mesothelioma had a median survival of 13.1 months compared with 5.7 months for patients with stage IV disease (25) . Also, patients with better performance status of ECOG 0-1 showed better OS of 11 months compared with ECOG 2 with median OS 8 months and ECOG 3 with only 2 months median OS (P value 0.001).…”
Section: Discussionmentioning
confidence: 65%
“…this is similar to the correlation found in chinese study involving 1110 MPM patients showing median survival time was 17, 13, 12, 8, 6, 5 months for IA, IB, II, IIIA, IIIB, and IV, respectively (19) . This is also evident in a Dutch study conducted among 12,168 patients showed that patients diagnosed with stage I pleural mesothelioma had a median survival of 13.1 months compared with 5.7 months for patients with stage IV disease (25) . Also, patients with better performance status of ECOG 0-1 showed better OS of 11 months compared with ECOG 2 with median OS 8 months and ECOG 3 with only 2 months median OS (P value 0.001).…”
Section: Discussionmentioning
confidence: 65%
“…van Kooten JP et al [8] retrospectively analyzed 629 MPM patients registered at the National Cancer Center in the Netherlands from 1993 to 2018, and it showed that the survival rate of MPM patients who received chemotherapy and/or surgery was close to zero after 3 years of follow-up. Therefore, this study used 3 years (The length of time required to receive clinical treatment) as the observation period for MPM patients.…”
Section: Malignant Peritoneal Mesothelioma (Mpm) Prevalence In Chinamentioning
confidence: 99%
“…The Netherlands ranks in the top five worldwide regarding the incidence of mesothelioma (46,47). Mesothelioma is strongly correlated with asbestos use (46)(47)(48), which application peaked between 1970 and 1980 (49). Since 1993, use of asbestos is legally prohibited in the Netherlands.…”
Section: Surgical Treatment Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…Since 1993, use of asbestos is legally prohibited in the Netherlands. Nevertheless, the long-term effects are present in daily practice with an incidence in 2018 of 3.3 cases per 100,000 person-years ( 49 ). Treatment of mesothelioma is performed in tertiary centers.…”
Section: Performance Of Dutch Thoracic Surgery Centersmentioning
confidence: 99%